2018
DOI: 10.1530/rep-17-0732
|View full text |Cite
|
Sign up to set email alerts
|

LIFR increases the release of soluble endoglin via the upregulation of MMP14 expression in preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-specific disorder that is the main cause of maternal and perinatal morbidity and mortality worldwide. Inadequate trophoblastic invasion and endothelial dysfunction in the placenta are considered the foundation of the pathogenesis of preeclampsia in which soluble endoglin (sENG) plays an antiangiogenic role in the development of PE. The leukemia inhibitory factor receptor (LIFR) has been widely studied and is highly involved in arterial injury and in the migration of cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Studies have shown that 65Da sEng monomer in the placenta of patients with preeclampsia is four times higher than normal pregnant patients . The mechanism by which sEng participates in the pathophysiological process of preeclampsia is not well understood . sEng is almost undetectable in non‐pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that 65Da sEng monomer in the placenta of patients with preeclampsia is four times higher than normal pregnant patients . The mechanism by which sEng participates in the pathophysiological process of preeclampsia is not well understood . sEng is almost undetectable in non‐pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…31 The mechanism by which sEng participates in the pathophysiological process of preeclampsia is not well understood. 11,[32][33][34] sEng is…”
Section: Discussionmentioning
confidence: 99%
“…These included annexin A5 (ANXA5) an anticoagulant protein, inhibin beta A chain (INHBA), which is a subunit of both inhibin and activin, transthyretin (TTHY) a thyroid hormone-binding protein, insulin-degrading enzyme (IDE), which binds to insulin and leukaemia inhibitory factor receptor (LIFR). Whilst proteins like ANXA5, inhibins/activins, TTHY and LIFR have been previously reported to be secreted from the placenta 15,4547 , we are not aware of any studies describing the secretion of other proteins, like IDE from the human placenta. Furthermore, other secreted proteins such as adipocyte enhancer-binding protein 1 (AEBP1) and Y-box-binding protein 1 (YBOX1), which can regulate transcription were also detected in the placental secretome.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the placenta secretes inhibins, activins and relaxins, which aid in the adaptation of the endocrine, renal, circulatory and immune systems of the mother during gestation 13,14 . Finally, the placenta secretes proteases, inhibitors of peptidases, binding proteins and soluble forms of receptors for steroids, growth factors, cytokines and circulating factors, like lipoproteins, which contribute to the pleiotropic endocrine regulation of maternal physiology during gestation and show some predictive value for conditions like IUGR 1518 . Thus, there is likely a constellation of protein mediators secreted by the placenta that facilitate maternal adaptations and ensure adequate fetal growth, required for a healthy pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%